2007
DOI: 10.1111/j.1442-2050.2007.00702.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful endoscopic hemoclipping of an esophageal perforation

Abstract: We describe a case of esophageal perforation that resulted from a fishbone. A 71-year-old man had had a fishbone impacted in the lower esophagus for 2 days. At presentation, the bone was dislodged at endoscopy; one round opening in a deep ulceration was detected when the fishbone was removed. The perforation was closed by endoscopic hemoclipping, after the removal of the fishbone. A thoracic computed tomography revealed air around the esophagus, aorta and bronchus and the presence of a pleural effusion. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
4
0
2
Order By: Relevance
“…Under such circumstances, the length of hospital stay increases. Some surgeons now prefer to use nonsurgical procedures 36,37 . The principles of treatment entail the endoscopic approach: the insertion of covered self‐expandable stents, the use of clips, and the injection of fibrin glue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under such circumstances, the length of hospital stay increases. Some surgeons now prefer to use nonsurgical procedures 36,37 . The principles of treatment entail the endoscopic approach: the insertion of covered self‐expandable stents, the use of clips, and the injection of fibrin glue.…”
Section: Discussionmentioning
confidence: 99%
“…Some surgeons now prefer to use nonsurgical procedures. 36,37 The principles of treatment entail the endoscopic approach: the insertion of covered self-expandable stents, the use of clips, and the injection of fibrin glue. Endoscopic repair using the hemoclip device seems to be safe and effective.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as perforation area, degree of contamination, time after perforation and presence of comorbidity have prognostic values in these patients whose morbidity and mortality is high. [5] Symptoms may be atypical in terms of the localisation of the oesophagus perforation, or they may imitate other diseases (including myocardial infarction, spontaneous pneumothorax or aortic dissection); furthermore, there may be a delay in diagnosis. [6] It has been shown that misdiagnosis or delayed diagnosis rate may be >50%.…”
Section: Discussionmentioning
confidence: 99%
“…Böylece hastane yatış süre-si ve morbidite artar. Bu dezavantajlar nedeniyle son zamanlarda özofagial perforasyonlarda cerrahisiz tedaviye yönelen otörler olmuştur (73)(74)(75)(76)(77)(78)(79). Tedavi prensiplerinde fibrin glue enjeksiyonu, klips kullanı-mı ve kendiliğinden genişleyebilen kaplı stentler gibi endoskopik işlemlere doğru meyil olmaya başlamıştır.…”
Section: Minimal İnvaziv Tekniklerunclassified